DISTRACTION FOREARM BONE GRAFT CHARACTERISTICS IN EXPERIMENT WITH STIMULATION OF BIOLOGICALLY ACTIVE POINTS - I. N. Mikhailov; V. Y. Lebedinskiy; M. E. Puseva; Y. S. Netiosin (Acta Biomedica Scientifica, 2015)
During our experimental study, we researched peculiarities of formation and remodeling of distraction forelimb bone graft in rabbits at insertion of transosseous elements through acupuncture points (stimulation of biologically active points). One of the forelimbs was lengthened on 10 mm by Ilizarov method. Using morphoscopy and morphometry we studied morphofunctional changes in the bone regenerate at different stages of experiment during stimulation of biologically active points and compared these quantitative characteristics with parameters of the intact bone.